In vitro, ex vivo and in vivo antihypertensive evaluation of enzymatic hydrolysates of Californian red worm (Eisenia fetida) proteins (2024)
ABSTRACT: Hypertension is an important risk factor concomitant with cardiovascular disease (CVD) states, which is why we set out to evaluate Californian red worm hydrolysates on antihypertensive activity both in vitro, ex vivo, using rabbit aortic rings and in vivo using hypertensive induced rats. The worms were manually separated, washed with water, purged for 4 h with 4 % sodium bicarbonate, sacrificed with 7 % saline, and finally washed with drinking water. The in vitro antihypertensive capacity was performed by measuring angiotensin-converting enzyme inhibition; for the ex vivo assays, rabbit aorta was used to measure relaxation; for the in vivo assays, rats with induced hypertension were used to perform acute (hypotension) and chronic assays, using captopril as a control in all assays. With respect to angiotensin-converting enzyme (ACE) inhibition, the EC50 value of the worm hydrolysate was found to be 358 ppm; with respect to the analysis in aortic rings, it was found that the mechanisms of action of the hydrolysate are endothelium-dependent, presenting a maximum relaxation of 35 %. With respect to the in vivo assays, the hypotensive test showed that the hydrolysate can reduce blood pressure by up to 32 % in only 2 h, while the chronic analysis showed that the hydrolysate at 150 ppm did not present statistically significant differences with the control (captopril) during the 15 days of analysis. The Red Californian earthworm hydrolysate presents bioactive compounds identified with antihypertensive activities in vitro, ex vivo and in vivo in different isolated and animal models. The study demonstrates the efficacy of the hydrolysate to be used as an alternative in the treatment and prevention of hypertension, and it can be implemented in functional foods or nutraceutical foods. Antihypertensive peptides, particularly those that inhibit angiotensin-converting enzyme (ACE), hold significant importance in medical research, specifically in the context of cardiovascular disease treatment, particularly hypertension. The focus on these peptides and the potential implications of their results in medical research can be summarized through several key points: 1) Mechanisms of Action-Antihypertensive peptides function by inhibiting ACE or renin, crucial enzymes in blood pressure regulation. 2)Alternatives to Synthetic Drugs, 3) Additional Health Benefits, and various other factors.